What Matters in Rural and Microfinance - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2005)
Due to the overall failure of donor-driven subsidized directed credit administered by government-owned development finance institutions, the emphasis in development policy has shifted to (rural) financial systems development and the building of self-reliant, sustainable institutions. While savings-based self-help groups and member-managed small cooperatives are more appropriate to remote and marginal areas, there is little to further differentiate rural and urban microfinance. Regardless of ownership, type of institution, and rural or urban sphere of operation, they ultimately all have to: - Mobilize their own resources through savings - Have their loans repaid - Cover their costs from their operational income - Finance their expansion from their profits. Three worlds of finance continue to exist, in which donors may intervene in very different ways: - The old world of donor-driven development finance, which need to be transformed into sustainable institutions - A new world of development finance, comprising viable formal and semiformal institutions with a commercial orientation, which do not, or not fully, rely on donor support for expansion - Informal financial institutions of ancient or recent origin, based on principles of self-reliance and viability with their potential for innovation and mainstreaming, to which donors may contribute.. There a numerous notable new developments in R/MF; but in the majority of countries, there are still major shortcomings that call for country-driven, coordinated interventions. Donors with their projects are found in both worlds; but there is an overall move from the old world of supply-driven development finance to the new world of demand-driven commercial finance.
Keywords: 330